2021
DOI: 10.1002/brb3.2184
|View full text |Cite
|
Sign up to set email alerts
|

The differential diagnostic value of a battery of oculomotor evaluation in Parkinson's Disease and Multiple System Atrophy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…In contrast to latency and velocity parameters, the literature is quite rich with strong evidence of PD patients requiring multi-step saccades to reach the target (Shaikh et al, 2019, Blekher et al, 2009, Zhou et al, 2021Gorges et al 2013, which is in line with the present findings reported here, where the average number of saccades required to reach the pro-saccade targets was significantly greater in PD patients. In addition, our findings here indicate that the first saccade towards the target (for both short and large eccentricity targets) was closer to the target in HC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to latency and velocity parameters, the literature is quite rich with strong evidence of PD patients requiring multi-step saccades to reach the target (Shaikh et al, 2019, Blekher et al, 2009, Zhou et al, 2021Gorges et al 2013, which is in line with the present findings reported here, where the average number of saccades required to reach the pro-saccade targets was significantly greater in PD patients. In addition, our findings here indicate that the first saccade towards the target (for both short and large eccentricity targets) was closer to the target in HC.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, findings regarding peak velocity have been mixed, with a few studies finding faster velocities in PD (Lu et al, 2019;Grillini et al, 2020), whereas most other studies found no differences between PD and healthy control (Blekker et al, 2009;Stuart et al, 2013;Gorges et al 2013;Zhou et al, 2021;Gitchel et al, 2012). In the present study, we find peak and mean velocities to be significantly increased in PD patients (only uncorrected p-value for peak velocity) for short eccentricity targets only.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…There are differences between the pathophysiology and progression of MSA and Parkinson's disease (PD). However, symptoms overlap between the two conditions in the early stages, making clinical diagnosis difficult (Zhou et al., 2021 ). Traditional anti‐PD medications have limited effectiveness against MSA.…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of saccadic movements during SPEM is considered normal, their frequency, extent, and type are different in patients with PD compared to normal subjects [9]. Several types of abnormal and involuntary saccadic movements have been reported in the literature [9], namely corrective saccades, which are elicited to eliminate existing delays when SPEM lags with respect to a moving target; anticipatory saccades, a type of ballistic movements that anticipate future target positions; and saccadic intrusions, which are involuntary movements taking the form of an initial fast movement away from the expected eye position followed by a return secondary saccade or a drift. The presence of these corrective movements leads to a detectable decrease in saccade amplitude and increased saccade latency, as well as a slightly impaired smooth pursuit with catch-up saccades [10].…”
Section: Introductionmentioning
confidence: 99%